2012
DOI: 10.5539/jas.v4n7p111
|View full text |Cite
|
Sign up to set email alerts
|

Technological and Financial Assessment of Small Scale Palm Oil Production in Kwaebibrem District, Ghana

Abstract: A study was carried out in the Kwaebibrim District of the Eastern Region of Ghana to study the production practices and the profitability of palm oil production among small scale processors using focus group discussions, semi-structured interviews and participant observations. Three categories of processing equipment namely digester screw press combined, digester with separate hand operated hydraulic press and digester with separate hand operated screw press were found in the district with the latter constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Palm oil processing through small-and medium-sized firms offers viable opportunities for local people, particularly women, to improve their livelihoods and to raise incomes from agricultural production and related enterprises. Ghana produces 232,700 MT of crude palm oil (MASDAR, 2010) annually, which is used for food and other industrial purposes, which originates for about 80% from the small-scale processing sector (Adjei-Nsiah, Sakyi-Dawson, & Kuyper, 2012;Adjei-Nsiah, Zu, et al, 2012). A case study of a medium-scale firm in the eastern region of Ghana (Adjei and Vellema, forthcoming), operating since 30 years, demonstrates a combination of processing and trading palm oil and other related products for the domestic market and (mostly) for the ethnic markets in Europe, where the firm competes with producers from other West African and Asian countries.…”
Section: Case From Ghanamentioning
confidence: 99%
“…Palm oil processing through small-and medium-sized firms offers viable opportunities for local people, particularly women, to improve their livelihoods and to raise incomes from agricultural production and related enterprises. Ghana produces 232,700 MT of crude palm oil (MASDAR, 2010) annually, which is used for food and other industrial purposes, which originates for about 80% from the small-scale processing sector (Adjei-Nsiah, Sakyi-Dawson, & Kuyper, 2012;Adjei-Nsiah, Zu, et al, 2012). A case study of a medium-scale firm in the eastern region of Ghana (Adjei and Vellema, forthcoming), operating since 30 years, demonstrates a combination of processing and trading palm oil and other related products for the domestic market and (mostly) for the ethnic markets in Europe, where the firm competes with producers from other West African and Asian countries.…”
Section: Case From Ghanamentioning
confidence: 99%
“…This prevents them from accessing the huge unsatisfied demand for high-quality oil in the remunerative market that exists both locally and externally. A study by Adjei-Nsiah et al (2012) has shown that processors in Ghana make little or no profit during the peak fruit production season due to lack of remunerative market for the oil. Lack of knowledge about good processing practices and inaccessibility to extension services are partly to be blamed for the poor processing practices by small scale processors.…”
Section: Technical Constraintsmentioning
confidence: 99%
“…Taiwo et al (2000) also reported that sterilising was done in open drums. Adjei-Nsiah et al (2012) in a study of 90 small-scale processors in the Kwaebibrem district of Ghana also reported that the threshing operation was done manually and that the fruits were sterilised in open drums.…”
Section: Sterilisationmentioning
confidence: 94%
“…This could be the reason why only a few horizontal digesters were adopted by the processors in the study area. However, Adjei-Nsiah et al (2012) reported that the digester and the digester screw press were used by 87% and 13% of the small-scale processors, respectively, in the Kwaebibrem District of Ghana.…”
Section: Digestionmentioning
confidence: 96%
See 1 more Smart Citation